2020
DOI: 10.1186/s12917-020-02464-7
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocowpox virus infection in an American bison (Bison bison)

Abstract: Background: The present report describes a case of pseudocowpox virus (PCPV) infection in a seven-year-old female bison euthanized due to a history of declining condition and sores on the vulva and udder. Case presentation: External examination revealed multifocal, raised, keratinized plaques (0.5-2 cm) covering the skin of the ventral surface of the tail, perineum, caudoventral abdomen, udder, both inguinal recesses, and the medial aspects of both thighs. No significant gross lesions were present in the remin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Molecular genetic analysis revealed that the causative agent of the disease in animals was pseudocowpox virus [ 3 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular genetic analysis revealed that the causative agent of the disease in animals was pseudocowpox virus [ 3 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudocowpox virus is detected in cattle, American bison, water buffalo, camels, and cats (3,58,101,172). Some tick species that are collected from cattle are found to be positive for pseudocowpox virus by PCR, indicating that ticks can play a role in pseudocowpox virus epidemiology (35,141).…”
Section: Pseudocowpox Virusmentioning
confidence: 99%
“…In experimental infection, hyperemic foci, ulceration, fibrinotic and scabby lesions were observed on the muzzle and lips of calves (54). Pseudocowpox virus infection is exhibited as multiple cutaneous nodules on the skin which are wart-like, proliferative, and keratinized in an American bison (172). In water buffalos, pseudocowpox symptoms are peeling of the tongue epithelium and oral ulcers (101).…”
Section: Pseudocowpox Virusmentioning
confidence: 99%
“…Other genuine PPV have been found in wildlife ruminants leading to the fourth established species, PPV of red deer ( Friederichs et al, 2015 ; Robinson and Mercer, 1995 ). In addition, PPV infections were described in reindeer, bison, muskox, Bactrian and dromedary camel and in marine mammals ( Dalton et al, 2023 ; Hautaniemi et al, 2010 ; Khalafalla, 2021 ; Shivanna et al, 2020 ). The latter are proposed as PPV species of pinnipeds ( Badr et al, 2022 ; Costa et al, 2021 ; Günther et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%